Antioxidant Activity and Chemical Composition of the Essential oil of Ducrosia anethifolia (DC.) Boiss. from Neyriz (Journal of Medicinal Plants and By-products, 2014)
Ducrosia anethifolia (DC.) Boiss. is belongs to the Apiaceae family. It is one of the three species of Iranian Ducrosia Boiss. species growing wild in several areas of the country. In this research, we extracted the essential oil and it analyzed by GC/MS. The analysis of essential oil from leaves of D. anethifolia about 19 constituents was identifed and percentage composition was determined (94.9%). The major constituents identified by this method were α-pinene (70.3%), β-myrcene (6.9%), β-pinene (6.3%), limonene (4.9%). So, extracts of this species extracted by maceration method and antioxidant activity evaluated by 1,1-diphenyl-2-picrylhydrazyl (DPPH•). Results showed that antioxidant activity of D. anethifolia in ethanolic and ethyl acetate extracts are less than Butylated hydroxytoluene (BHT) as a synthetic antioxidant which used for positive control. Although, antioxidant activity of ethanolic extract is more than ethyl acetate extract, but inhibitory power of this extracts is low.